2021
DOI: 10.1016/j.jsxm.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Pain: A Study on the Variance of Pain Thresholds Within BDSM Interactions in Dominants and Submissives

Abstract: Background BDSM is an acronym describing bondage and discipline, dominance and submission, and sadism and masochism. Afflicting or receiving pain is usually an important part of the BDSM interaction. Aim This research will focus on better understanding the aspect of pain within a BDSM interaction. Methods Submissive and dominant counterparts of 35 couples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…Another study (Pollok et al, 2010 ) reported an increase in pain thresholds evoked by laser stimuli in a small group of subjects with MB ( n = 10). Consistent with these results, a more recent study (Wuyts et al, 2021 ) reported an increase in the HPT, but not in the pressure pain threshold in subjects with MB. By contrast, Kamping et al ( 2016 ) found no significant difference in the pain threshold evoked by laser stimuli between subjects with MB and controls, consistent with our finding of normal thermal (heat and cold) pain thresholds and electrical pain and tolerance thresholds in men with MB.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Another study (Pollok et al, 2010 ) reported an increase in pain thresholds evoked by laser stimuli in a small group of subjects with MB ( n = 10). Consistent with these results, a more recent study (Wuyts et al, 2021 ) reported an increase in the HPT, but not in the pressure pain threshold in subjects with MB. By contrast, Kamping et al ( 2016 ) found no significant difference in the pain threshold evoked by laser stimuli between subjects with MB and controls, consistent with our finding of normal thermal (heat and cold) pain thresholds and electrical pain and tolerance thresholds in men with MB.…”
Section: Discussionsupporting
confidence: 67%
“…One plausible explanation is that they reflect differences in the psychological profiles of the MB subjects included in the different studies. In both the study by Defrin et al ( 2015 ) and that by Wuyts et al ( 2021 ), changes in pain thresholds were associated with significantly lower catastrophizing scores in subjects with MB than in controls. By contrast, our subjects with MB had catastrophizing scores similar to those of controls.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Estas tendencias comportamentales se vuelven patológicas una vez que nos resultan disfuncionales; por ejemplo, si impiden el desenvolvimiento de nuestra salud. Apoyándonos en la literatura en adicciones (Kurt & Ronel, 2016;Maté, 2009;Pickard, 2020), daremos cuenta de tres niveles de explicación -el biológico, el psicológico y el sociológico -que nos permitirán comprender cómo un hábito incentivado por deseos masoquistas se torna o no patológico (Coluccia et al, 2016;Ellis, 2008;Gebhard, 2008;Goldstein, 1983;Kamel, 2008;Kamel & Weinberg, 2008;Krafft-Ebing, 1892;Kurt & Ronel, 2016;Moser & Levitt, 2008;Wuyts et al, 2021). Interactuamos constantemente con el dolor y lo desagradable y desde hace siglos se ha identificado que el dolor y el placer pueden mezclarse: …cuando el placer prevalece en estas mezclas, la parte del dolor que en ella es inferior produce cosquilleo y hace que se irrite ligeramente, mientras que la parte del placer, que es dominante, lo tensa y a veces lo hace saltar, e infundiéndose toda clase de colores, de gestos, de jadeos, provoca excitación total y le hace dar gritos de locura.…”
Section: Introductionunclassified